Early Human Lithic Technologies: Multiple Technical Histories from Africa to East Asia - (:unkn) unknown (My University, 2022)
Human evolution is narrowly linked with technical evolution since the very beginning. For decades it was commonly assumed that from a new hominin species came new cognitive abilities, leading to technological innovation. This hypothesis is no longer sustainable nowadays, seeing the large amount of new archaeological evidence. Besides attributing one culture for one species, the question of hominin dispersals out of the African continent is also largely debated.Although it is still difficult to establish a clear scenario for hominin dispersals in the Old world, we can now propose several models for explaining the question of technical emergence and technological evolution. Here we discuss the question of technical convergence and multiple technical histories, by crossing the archaeological evidence from the Early Stone Age throughout East Africa, Mediterranean Europe and Eastern Asia, the geographic areas where Oldowan lithic assemblages are common.Lithic assemblages, taken as a whole system containing stone tools, knapping techniques and their evolution are an important matter to understand local technical evolution. This evolution is ruled by many factors, such as environment adaptations (climate variability, raw material availability and access), technical traditions, that can be seen as a co-evolution with hominin species and populations.
Keywords: African Research